Assessment of different head tilt angles in volumetric modulated arc therapy for hippocampus-avoidance whole-brain radiotherapy - Yuan, Cuiyun; Xu, Sisi; Li, Yang; Quan, Enzhuo; Chen, Dongjie; Liang, Jun; Liu, Chenbin (Frontiers in Oncology, 2024)
In the field of radiation therapy for brain metastases, whole-brain hippocampus-avoidance treatment is commonly employed. this study aims to examine the impact of different head tilt angles on the dose distribution in the whole-brain target area and organs at risk. It also aims to determine the head tilt angle to achieve optimal radiation therapy outcomes.: CT images were collected from 8 brain metastases patients at 5 different groups of head tilt angle. The treatment plans were designed using the volumetric modulated arc therapy (VMAT) technique. The 5 groups of tilt angle were as follows: [0°,10°), [10°,20°), [20°,30°), [30°,40°), and [40°,45°]. The analysis involved assessing parameters such as the uniformity index, conformity index, average dose delivered to the target, dose coverage of the target, hot spots within the target area, maximum dose, and average dose received by organs at risk. Additionally, the study evaluated the correlation between hippocampal dose and other factors, and established linear regression models. Results: Significant differences in dosimetric results were observed between the [40°,45°] and [0°,10°) head tilt angles. The [40°,45°] angle showed significant differences compared to the [0°,10°) angle in the average dose in the target area (31.49±0.29 Gy vs. 31.99±0.29 Gy, p=0.016), dose uniformity (1.20±0.03 vs. 1.24±0.03, p=0.016), hotspots in the target area (33.64±0.35 Gy vs.34.42±0.49 Gy, p=0.016), maximum hippocampal dose (10.73±0.36 Gy vs. 11.66±0.59 Gy, p=0.008), maximum dose in the lens (2.82±1.10 Gy vs. 4.99±0.16 Gy, p=0.016), and average dose in the lens (1.93±0.29 Gy vs. 4.22±0.26 Gy, p=0.008). There is a moderate correlation between the maximum dose in the hippocampi and the PTV length (r=0.49, p=0.001). Likewise, the mean dose in the hippocampi is significantly correlated with the hippocampi length (r=0.34, p=0.04).The VMAT plan with a head tilt angle of [40°,45°] met all dose constraints and demonstrated improved uniformity of the target area while reducing the dose to organs at risk. Furthermore, the linear regression models suggest that increasing the head tilt angle within the current range of [0°,45°] is likely to lead to a decrease in the average hippocampal dose.